Effect of Different Media on in vitro Seed Germination and Seedling Development of Cymbidium aloifolium (L.) Sw. - Pradhan, Shreeti; Regmi, Tripti; Parmar, Gaurav; Pant, Bijaya (Nepal Journal of Science and Technology, 2013)
A comparative study on in vitro seed germination and seedling development of Cymbidium aloifolium (L.) Sw., an epiphytic medicinal orchid, was carried out on four different conditions of Murashige and Skoog (MS) and Knudson (KC) medium viz. full, ½. ¼ strength and medium supplemented with 0.5mg/l BAP (benzyl amino purine) and 0.5mg/l NAA (Naphthalene acetic acid). Varied response in terms of seed germination, protocorm formation and seedling development was observed on two different media. Medium supplemented with hormones favored optimum condition for the germination (approx. 90%) of seeds followed by full, ½ and ¼ strength on both MS & KC media. MS medium supplemented with 0.5mg/l BAP and 0.5mg/l NAA showed comparatively better response within 7 weeks of culture than other conditions of MS medium as well as KC medium. Based upon the results, it was found that MS medium was more effective than KC medium for germination, protocorm and plantlet formation. The present study has provided useful information that the high concentration of nutrient compounds supplemented with hormones are required for earlier in-vitro germination and plantlet development from immature seeds of C. aloifolium. It could be an important protocol to conserve this important orchid species by establishing an efficient in vitro regeneration system using immature seed culture. Nepal Journal of Science and Technology Vol. 14, No. 1 (2013) 51-56 DOI: http://dx.doi.org/10.3126/njst.v14i1.8878